198k views
1 vote
Given g(x)=-3x-3g(x)=−3x−3, solve for xx when g(x)=0g(x)=0.

User McMurphy
by
5.1k points

2 Answers

4 votes

Final answer:

To solve the equation g(x) = -3x - 3 = 0, set g(x) equal to zero and solve for x. The solution is x = -1.

Step-by-step explanation:

To solve the equation g(x) = -3x - 3 = 0, we set g(x) equal to zero and solve for x. Rearranging the equation, we have:

-3x - 3 = 0

Adding 3 to both sides:

-3x = 3

Dividing both sides by -3:

x = -1

Therefore, the solution to g(x) = 0 is x = -1.

User Ringding
by
5.2k points
4 votes

x = - 1

we require to solve - 3x - 3 = 0

add 3 to both sides

- 3x = 3

divide both sides by - 3

x =
(3)/(-3) = - 1


User Areuexperienced
by
5.7k points